AB1141 Prevalence of long-term steroid therapy: french data. (15th June 2017) - Couvaras, L; Trijau, S; Lamotte, G De; Pradel, V; Pham, T; Lafforgue, P
Abstract : Background: Corticosteroids are widely used for various diseases, from chronic respiratory conditions to auto-immune disorders. However, there are few epidemiological data about long-term steroid therapy in southern Europe (1, 2, 3). Objectives: To describe chronic glucocorticoid prescriptions in a large cohort. Methods: Information was collected from a national public health-insurance database that covers 4.1 million individuals and 83% of the population, in our geographic area of Provence-Alpes-Côte-d'Azur and Corsica, from September 1, 2009 through August 31, 2011. We identified subjects aged of 15 years and over starting glucocorticoid therapy. Chronic glucocorticoid therapy was defined as ≥7.5mg of prednisone equivalent per day during at least 90 days consecutive. We identified the incident cases of long-term glucocorticoid therapy, defined as those prevalent cases who did not fill glucocorticoid prescriptions during the first 6 months of the 24-month study period. Results: We identified 32, 812 patients who were prescribed glucocorticoid therapy, yielding 0.97% prevalence. Of these 32, 812 patients, 14, 205 (43.3%) met our definition of incident cases, yielding an incidence of 0.42% for 18 months in the overall population aged at least 15 years, corresponding to an incidence of long-term glucocorticoid therapy of 2.8/1000 inhabitants/year. Among these incident cases, the most currently prescribed glucocorticoids were prednisolone (64%) and prednisone (32%). Sixty-three per cent of patients received only one type of glucocorticoid while 33% received two and 5% received 3 or more of them. The average treatment duration was 270.9 days (CI 95% 267.7 – 274). Most prescriptions (55, 4%) were initiated by general practitioners. The median prednisone-equivalent dose was 11mg/day (IQR, 8.8–17.8) and varied very little with age and sex. Rheumatoid arthritis was the most common disease associated with chronic glucocorticoid prescriptions in this cohort (30%), followed by chronic respiratory failure (21%), internal medicine diseases such as connectivite tissue diseases, polymyalgia rheumatica or Giant-cell arteritis (21%), asthma (15%) and infammatory bowel diseases like ulcerative colitis or Crohn's disease (13%). Conclusions: Long-term corticosteroid therapy is frequent in France, its description is close to what is already known in Europe. References: Overman RA, Heh JY, Deal CL. Prevalence of oral glucocorticoid usage in the United States: a general population perspective. Arthritis Care Res (Hoboken) 2013;65:294–8. Gudbjornsson B, Juliusson UI, Gudjonsson FV. Prevalence of long term steroid treatment and the frequency of decision making to prevent steroid induced osteoporosis in daily clinical practice. Ann Rheum Dis 2002;61:32–6. Fardet L, Petersen I, Nazareth I. Prevalence of long-term oral glucocorticoid prescriptions in the UK over the past 20 years. Rheumatology 2011;50:1982–90. Disclosure of Interest: None declared